THE INFLUENCE OF RECEIVED CREDIT, RESOURCE COMPETENCE AND INCOME OF MSMEs ON EMPLOYEE WELFARE - Baehaqi; M Amin (Jurnal Ekonomi, 2023)
The purpose of this study was to analyze the effect of credit received on employee welfare, human resource competency on employee welfare and MSME income on employee welfare. This research is a quantitative research carried out in West Nusa Tenggara Province in East Lombok Regency with a sample size of 80 respondents. Data analysis was carried out using the SEM-PLS method. research results and data analysis show that the relationship between credit received on employee welfare is not significant / credit received does not have an impact on employee welfare. Human resource competence has a significant impact on employee welfare/human resource competence has a positive impact on employee welfare. MSME income on employee welfare is significant / MSME income has a positive impact on employee welfare.